2021
DOI: 10.1002/hsr2.461
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between anxiety, stress, spiritual health, and mindfulness among patients undergoing hemodialysis: A survey during the COVID‐19 outbreak in Southeast Iran

Abstract: Background and aims Hemodialysis patients are prone to high stress and anxiety related to the acute coronavirus epidemic. Mindfulness and spiritual health are among the factors associated with stressful and anxious situations. The current study aimed to investigate the relationship between mindfulness, spiritual health, and coronavirus stress/anxiety in patients undergoing hemodialysis. Methods One hundred and forty‐four patients underwent hemodialysis participated in this cross‐sectional study. Patients compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 46 publications
0
7
2
Order By: Relevance
“…In contrast to the current study’s findings, Dehghan et al (2021a) showed that the study of mindfulness with the FMI scale was not associated with COVID-19 anxiety in cancer patients. However, high levels of mental and physical anxiety, as well as concern about COVID-19, have been observed in cancer patients, causing difficulties in their lives ( Dehghan et al, 2021b ).…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to the current study’s findings, Dehghan et al (2021a) showed that the study of mindfulness with the FMI scale was not associated with COVID-19 anxiety in cancer patients. However, high levels of mental and physical anxiety, as well as concern about COVID-19, have been observed in cancer patients, causing difficulties in their lives ( Dehghan et al, 2021b ).…”
Section: Discussioncontrasting
confidence: 99%
“…From a behavioral perspective, people with higher spirituality and religiosity are often committed to a healthier physical and mental lifestyle. All of them are directly related to happiness through controlling your mind ( Amirian and Fazilat-Pour, 2016 ; Zimmer et al, 2016 ; Dehghan et al, 2021a ). People in cultural and religious fields are happy and hope for a heavenly life.…”
Section: Discussionmentioning
confidence: 99%
“…Mindfulness refers to awareness by paying attention to the moment without making judgments about what you are doing, which can vary from moment to moment and from person to person (Malakoutikhah et al, 2021a). The positive effects of mindfulness in reducing psychological problems of individuals have been reported in several studies (Dehghan et al, 2021;Malakoutikhah et al, 2021b). According to a study, a mindfulness-based stress reduction program significantly increased CS and decreased BO in emergency personnel (Ducar et al, 2020).…”
Section: Introductionmentioning
confidence: 93%